Morbidity and mortality after fragility hip fracture surgery in patients receiving vitamin K antagonists and direct oral anticoagulants. Issue 166 (June 2018) - Frenkel Rutenberg, Tal; Velkes, Steven; Vitenberg, Maria; Leader, Avi; Halavy, Yael; Raanani, Pia; Yassin, Mustafa; Spectre, Galia
Abstract: Introduction: Early surgical treatment is recommended to reduce morbidity and mortality in patients with fragility hip fractures. Anticoagulation treatment poses a surgical challenge. While the action of vitamin K antagonists (VKAs) can be reversed, for direct oral anticoagulants (DOACs) antidote is only available for dabigatran. We aimed to assess the outcomes of patients treated with VKAs or DOACs undergoing surgical treatment for fragility hip fractures. Materials and methods: A retrospective study of patients presenting with proximal femoral fractures between January 2012 and June 2016. Patients with VKAs received vitamin-K. Primary outcomes were 1-year and in-hospital mortality. Secondary outcomes were time to surgery, in-hospital complications, need for blood transfusions and 1-year readmissions. Results: Seven-hundred seventy-nine patients (796 hips) were included; 103 received VKAs, 47 DOACs and 646 no-anticoagulation. No difference between the 3 groups was noted with respect to patients' demographics or surgery type. Charlson's comorbidity index was higher for the DOACs group. Patients under anticoagulation were delayed to theater (Surgery < 48 h in 51% DOACs and 59% VKAs patients vs. 92% of no-anticoagulation, p < 0.001). Neither in-hospital nor 1-year mortality differed between groups. No other outcome measures differed, except for more wound infections in VKAs patients. Conclusions: While preoperative anticoagulation delays surgery following fragility hip fractures, this delay was not found to be related to increased morbidity or mortality. DOACs-treated patients did not have adverse outcomes compared to VKAs-treated patients despite the irreversibility of their treatment. Highlights: Chronic anticoagulation treatment delays surgery for fragility hip fractures. The delay was not correlated with worse immediate or delayed outcomes. Patients' outcomes were similar regardless of the anticoagulation treatment type. Vitamin K antagonists and direct oral anticoagulants had similar effect on results.